Kepemimpinan Agile Dalam Menghadapi Tantangan VUCA di Era Digital - Anisa Nur Maulidiyah; Izzatul Masruroh; Mochammad Isa Anshori (BADAN PENERBIT STIEPARI PRESS, 2025)
Agile leadership has emerged as a strategic response to the challenges faced by organizations in the digital era, particularly within a VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) environment. The rapidly changing business landscape requires organizations to adapt quickly and make decisions with flexibility. Agile leadership offers an approach that emphasizes adaptability, collaboration, innovation, and the courage to experiment and learn from failure through the principle of